Application of methyl-TROSY to a large paramagnetic membrane protein without perdeuteration: (13)C-MMTS-labeled NADPH-cytochrome P450 oxidoreductase - Galiakhmetov, Azamat R (J Biomol NMR, 2017)
NMR spectroscopy of membrane proteins involved in electron transport is difficult due to the presence of both the lipids and paramagnetic centers. Here we report the solution NMR study of the NADPH-cytochrome P450 oxidoreductase (POR) in its reduced and oxidized states. We interrogate POR, first, in its truncated soluble form (70 kDa), which is followed by experiments with the full-length protein incorporated in a lipid nanodisc (240 kDa). To overcome paramagnetic relaxation in the reduced state of POR as well as the signal broadening due to its high molecular weight, we utilized the methyl-TROSY approach. Extrinsic (13)C-methyl groups were introduced by modifying the engineered surface-exposed cysteines with methyl-methanethiosulfonate (MMTS). Chemical shift dispersion of the resonances from different sites in POR was sufficient to monitor differential effects of the reduction-oxidation process and conformation changes in the POR structure related to its function. Despite the high molecular weight of the POR-nanodisc complex, the surface-localized (13)C-methyl probes were sufficiently mobile to allow for signal detection at 600 MHz without perdeuteration. This work demonstrates a potential of the solution methyl-TROSY in analysis of structure, dynamics, and function of POR, which may also be applicable to similar paramagnetic and flexible membrane proteins.